Entre el silenci i l’esgarip a La salvatge, d’Isabel-Clara Simó - Maria Sevilla Paris (Catalonia)
This article proposes a reading of La salvatge. Elegia de Dolores Mendoza (1994), by Isabel-Clara Simó, following two key concepts of the novel: on the one hand, that of savagery, understood as a representational exile that relegates the female characters of the story to the margins of discourse, both literally and figuratively. On the other hand, that of domestication, or imposition of the masculine order through the use of control, surveillance, and the logic of exchange. The study develops these two topics from the analysis of the characters but also in light of some of the most outstanding poetic and narratological resources of the novel, all under the theoretical frame of authors such as Maria-Mercè Marçal, Montserrat Roig and Judith Butler.